The consequences of narrow framing for risk-taking: A stress test of myopic loss aversion - Rene Schwaiger; Markus Strucks; Stefan Zeisberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
Narrow bracketing in combination with loss aversion has been shown to reduce individual risk-taking. This is known as myopic loss aversion (MLA) and has been corroborated by many studies. Recent evidence has contested this notion indicating that MLA's applicability is confined to highly artificial settings. Given the impact of these findings, we reevaluated the evidence on MLA involving a total of 2,245 university students, thereby achieving substantially higher statistical power than in almost all previous studies. To clarify inconsistencies in the literature, specifically under more realistic investment environments, we systematically modified the seminal study design by Gneezy and Potters (1997) to include five key adjustments. These involved realistic, down-scaled returns, return compounding, and extended investment horizons. Contrary to some prior studies that have raised doubts about the robustness of MLA, our results-which are highly robust to analytical heterogeneity-consistently document the presence of MLA across all experimental conditions. Our findings substantiate the widespread applicability of MLA and underscore the benefits of disclosing aggregated returns in practical financial decision-making contexts.
Keywords: D14; D81; G02; G11; 330; myopic loss aversion; narrow framing; risk-taking; meta science; replication